2011
DOI: 10.3389/fnhum.2011.00114
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Double-Pulse TMS of the Posterior Parietal Cortex on Reflexive and Voluntary Saccades

Abstract: Gap and overlap tasks are widely used to promote automatic versus controlled saccades. This study examines the hypothesis that the right posterior parietal cortex (PPC) is differently involved in the two tasks. Twelve healthy students participated in the experiment. We used double-pulse transcranial magnetic stimulation (dTMS) on the right PPC, the first pulse delivered at the target onset and the second 65 or 80 ms later. Each subject performed several blocks of gap or overlap task with or without dTMS. Eye m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Variability of eye movement parameters is approximately 20% in healthy adults. 53 Variability increases in the elderly, as well as in patients with neurodegenerative disorders. 44 , 54 , 55 The present study suggested that variability is a biomarker of the vergence disorder and the Vd-s rehabilitation protocol acts primarily on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Variability of eye movement parameters is approximately 20% in healthy adults. 53 Variability increases in the elderly, as well as in patients with neurodegenerative disorders. 44 , 54 , 55 The present study suggested that variability is a biomarker of the vergence disorder and the Vd-s rehabilitation protocol acts primarily on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Below, we present the effects of age on each of the experimental paradigms for which a significant effect is present. As we mentioned earlier, Kapoula et al (2011) propose that the cortical and subcortical circuits and mechanisms involved in programming saccade are different according to the initiation mode, automatic or more controlled. In the case of automatic saccades (gap paradigm), these circuits will involve mainly the parietal lobe, whereas in the case of controlled saccades (overlap paradigm), the frontal lobe seems activated (Pierrot-Deseilligny et al, 1995Gaymard 2012).…”
Section: Age Effectmentioning
confidence: 98%
“…a longer circuit of oculomotor command. Kapoula et al (2011) argued that in the overlap test saccade preparation is done via the FEF similarly to voluntary saccades discussed by Pierrot-Deseilligny. Other researchers (Isa and Kobayashi 2004) proposed models that give an important role to the superior colliculus for the initiation of the saccade in the gap paradigm.…”
Section: Gap Versus Overlap Tasksmentioning
confidence: 99%
See 2 more Smart Citations